Hydro‐Chemical Conditions of Shaping the Water Quality of Shallow Łęczna‐Włodawa Lakes (Eastern Poland). Issue 5 (16th March 2017) - Ferencz, Beata; Toporowska, Magdalena; Dawidek, Jarosław; Sobolewski, Wojciech
Abstract : Although water quality has been the main concern of ecologists over the last decades, a deterioration of both the quality and quantity of water has been observed worldwide. Understanding the dominant processes shaping eutrophication processes is crucial to sustainable water management in lake catchments. The aim of the study was to determine the importance of elements of lake‐catchment system structures in the processes of shaping lake water quality. The values of loads delivered to the lake basins from their catchments as well as nutrient output were calculated on the basis of stream discharge and nutrient concentration. A range of hydro‐chemical influences of each stream was presented by means of a range of a radius. A model of nutrient transport (prepared in GIS software) was used in the catchment of a lake without tributaries. Additionally, phytoplankton abundance and water quality indices were calculated. The results showed a clear pattern for the following lakes, Syczyńskie > Pniówno > Chuteckie > Tarnowskie, in terms of nutrient load as well as water quality. The hydro‐chemical influence of lake tributaries was determined by runoff processes, which reflected catchment geology, relief, and flushing time. The Q index showed a good ecological status for lakes Chuteckie and Tarnowskie, moderate for Lake Pniówno, and poor for Lake Syczyńskie. Abstract : The importance of factors shaping lakes' water quality has been expressed on the basis of nutrient loads input and output, the mass of ions retained or lost in a lake basin, the range of hydrochemical zones of streams' influence, and hydrobiological state of lake water. The presented lake‐catchment mechanisms are essential for the rational management of water resources, both quantitative and qualitative.